THE EFFECT OF THE PROJECT-BASED LEARNING MODEL CONTAINING SUBAK LOCAL WISDOM ON STUDENTS' CREATIVE THINKING ABILITIES AND SCIENCE LEARNING OUTCOMES - Ni Komang Ayu Sekarini; I Wayan Suja; I Wayan Muderawan (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to (1) describe and explain the effect of implementing the PjBL model containing local wisdom of Subak on students' creative thinking skills and science learning outcomes, (2) describe and explain the effect of implementing the PjBL model containing local wisdom of Subak on students' creative thinking skills, and (3) describe and explain the effect of implementing the PjBL model containing local wisdom of Subak on students' science learning outcomes. The population in this study were 287 students of class VII of SMP Negeri 14 Denpasar. The sample was determined using the cluster technique. random sampling from the population and obtained a sample of 164 students (4 classes). The research design used a nonequivalent pretest-posttest control group design . Data collection used a test instrument. Data were analyzed using descriptive statistics and inferential Multivariate Analysis of Covariance (MANCOVA) with a significance level of 5%. To determine the magnitude of the influence obtained, after the MANCOVA test, it was continued with an effect size test . The results of the study were: (1) students who learned using the PjBL model containing local wisdom of Subak had better creative thinking skills and science learning outcomes than students who learned with the PjBL model, (2) students who learned using the PjBL model containing local wisdom of Subak had better creative thinking skills than students who learned with the PjBL model, (3) students who learned using the PjBL model containing local wisdom of Subak had better science learning outcomes than students who learned with the PjBL model.